1992
DOI: 10.1039/c39920000526
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bending modes on the intramolecular electron-transfer rates of mixed-valence 1′,3′,1‴,3‴-tetraethyl- and 1′,2′,1‴,2‴-tetraethyl-biferrocenium triiodides

Abstract: The results of an X-ray structure determination of 1 ',3',1 "',3"'-tetraethylbiferrocenium triiodide, the effects of changing the relative positions of ethyl substituents from 1 ',3',1 "',3"' t o 1 ',2'"''',2'" o n the intramolecular electron-transfer rates of biferrocenium salts in the solid state, and a theoretical explanation of the influence of steric factors o n the electron-transfer rates are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Furthermore, compound 11 has a valence-trapped electronic structure at temperatures below 150 K and becomes a valence-detrapped electronic structure at a temperature of ∼200 K. In comparison with para-substituted compounds ( 10 − 12 ), a valence-detrapped electronic structure is seen even at 77 K for ortho-substituted mixed-valence compounds of 13 and 14 . We suggested that relatively minor perturbations caused by interactions between neighboring cations and anions have pronounced effects on electron transfer. ,
1
…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, compound 11 has a valence-trapped electronic structure at temperatures below 150 K and becomes a valence-detrapped electronic structure at a temperature of ∼200 K. In comparison with para-substituted compounds ( 10 − 12 ), a valence-detrapped electronic structure is seen even at 77 K for ortho-substituted mixed-valence compounds of 13 and 14 . We suggested that relatively minor perturbations caused by interactions between neighboring cations and anions have pronounced effects on electron transfer. ,
1
…”
Section: Introductionmentioning
confidence: 93%
“…We suggested that relatively minor perturbations caused by interactions between neighboring cations and anions have pronounced effects on electron transfer. 22,[28][29][30] A recent interesting finding is that there is a significant influence on the electron-transfer rate in the mixedvalence biferrocenium salts (15-18) when the cyclopentadienyl (Cp) rings in each ferrocenyl moiety are tilted from a parallel relation between the two Cp rings around the Fe ion. Such a structural modification would lead to greater metal-ligand interactions as the rings tilt.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an interesting finding was reported that there is a significant influence on the electron-transfer rate in mixed-valence biferrocenium triiodide salts when the two cyclopentadienyl (Cp) rings associated with each ferrocenyl moiety are tilted from a parallel geometry. Such a structural modification of the coplanar relation between the two Cp rings around the Fe ion leads to greater metal−ligand interactions as rings tilt. We previously suggested 4 that the difference in electron-transfer rates for the series of alkylbiferrocenium cations ( 1 − 3 ; Chart ) is mainly due to the degree of tilting of the Cp rings.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported systematic studies for ET in the solid state for a series of mixed-valence biferrocenium cations ( 1 − 8 ), which have led to a wealth of new experimental results. Major progress has been made in studying the dependence of ET rates on the lattice dynamics 3-6 and on the cation−anion interactions, as well as on the structural micromodification . More recently, we prepared a series of polyalkylbiferrocenium triiodide salts ( 9 − 14 ) to study the influence of ring tilt between two least-squares-fitted cyclopentadienyl (Cp) rings on ET and to investigate energetic control of ET rates. Deviations of the Cp rings from the parallel position were found to correlate quite well with the critical temperature for electronic delocalization−localization in mixed-valence biferrocenium salts.…”
Section: Introductionmentioning
confidence: 99%